Titanium dioxide nanoparticle incorporated PVDF-HFP based composite membrane for direct methanol fuel cells application - Karim, MA (Bangladesh Journal of Scientific and Industrial Research, 2021)
Two composite polymeric membranes were synthesized using poly vinylidene fluoride-hexafluoroprropylene (PVDF-HFP) host in polyvinyl alcohol and with or without TiO2 nanoparticlesas a porous substrate. The structure of the membranes was PDVF-HFP/PVA and PVDF-HFP/PVA/TiO2.The composition of the synthesized membranes was analyzed by FTIR spectrum.The porosity of the polymer membranes were measured by immersing the membranes into n-butanol. The conductivity of the composite membranes was determined by impedance spectroscopy and the methanol permeability of the membranes was obtained from diffusion experiments. The surface morphology images were investigated by scanning electron microscope(SEM). The SEM image of the composite membrane incorporated with TiO2 has many pores which increased the conductivity of the membrane as compared to non TiO2 incorporated one. The composite membrane with TiO2 showed a good balance between proton conductivity and methanol permeability. The cell with PVDF-HFP/PVA/TiO2 composite membrane showed higher power density. Bangladesh J. Sci. Ind. Res.56(2), 125-132, 2021